2023
DOI: 10.1001/jamanetworkopen.2023.27351
|View full text |Cite
|
Sign up to set email alerts
|

Germline Variants Incidentally Detected via Tumor-Only Genomic Profiling of Patients With Mesothelioma

Abstract: ImportancePatients with mesothelioma often have next-generation sequencing (NGS) of their tumor performed; tumor-only NGS may incidentally identify germline pathogenic or likely pathogenic (P/LP) variants despite not being designed for this purpose. It is unknown how frequently patients with mesothelioma have germline P/LP variants incidentally detected via tumor-only NGS.ObjectiveTo determine the prevalence of incidental germline P/LP variants detected via tumor-only NGS of mesothelioma.Design, Setting, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…With increasing scrutiny, the list of potential pathogenic germline variants associated with mesothelioma is expanding. So far, potential mutations have been identified in over 80 genes, including in known tumour suppressor genes and genes associated with other hereditary cancer syndromes, DNA maintenance and repair as well as genes commonly somatically mutated in mesothelioma (review in [ 23 ]) [ 24 ]. The prevalence of pathogenic germline variants in the entire mesothelioma cohort is difficult to estimate, given that many of the studies designed to identify such genetic susceptibility markers have been in cohorts enriched based on having a family history of cancer.…”
Section: Bap1 Tumour Predisposition Syndromementioning
confidence: 99%
“…With increasing scrutiny, the list of potential pathogenic germline variants associated with mesothelioma is expanding. So far, potential mutations have been identified in over 80 genes, including in known tumour suppressor genes and genes associated with other hereditary cancer syndromes, DNA maintenance and repair as well as genes commonly somatically mutated in mesothelioma (review in [ 23 ]) [ 24 ]. The prevalence of pathogenic germline variants in the entire mesothelioma cohort is difficult to estimate, given that many of the studies designed to identify such genetic susceptibility markers have been in cohorts enriched based on having a family history of cancer.…”
Section: Bap1 Tumour Predisposition Syndromementioning
confidence: 99%
“…However, while the incidence of mesothelioma × 100,000 persons is decreasing, the overall number of mesotheliomas has not declined significantly, at least not in the USA as the total population is increasing. Presently mesotheliomas are occurring for a combination of several factors: (1) the presence of asbestos in old constructions that in some cases can result in substantial exposure; (2) the development of rural areas containing asbestos and other carcinogenic fibers, which have caused exposure in workers first and residents later [ 9 , 12 14 ] (3) the discovery that 12–16% of mesotheliomas are linked to germline mutations [ 15 17 , 24 , 25 ]; (4) the development and use of radiation therapy in the past decades to treat several malignancies, which may cause mesothelioma years later [ 22 , 23 , 26 , 27 ]; (5) in addition, mesothelioma, like most other cancers, affects prevalently old people. The population in industrialized countries is increasing and growing older, and thus the number of people most susceptible to developing mesothelioma is increasing [ 6 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Moreover, we and others found that mutations of additional tumor suppressor genes, including BRCA1, BRCA2, TP53, BLM, etc., predisposed to mesothelioma. Overall, it is estimated that 12–16% of mesotheliomas develop in carriers of germline BAP1 mutations-the most common mutation, or of other tumor suppressor gene mutations [ 16 19 , 25 ]. Some of these mutations, like BAP1, have 100% cancer penetrance and thus are sufficient to cause cancer, others may increase susceptibility to asbestos and to other carcinogens present in the environment [ 21 , 52 ].…”
Section: Bap1 and Mesotheliomamentioning
confidence: 99%
“…[8][9][10] It is of great interest since it accounts for the most common somatic mutations in PM. 10,11 BAP1 mutations can also be inherited, and individuals with germline mutations in this gene have been widely recognized as being predisposed to the disease, although patients with a germline BAP1 mutation are associated with better prognosis. 11,12 By identifying germline mutation status solely through radiomics, clinicians can be prompted to pursue genetic testing that may not be readily conducted otherwise, 13 resulting in more streamlined patient prognostication and assessment of family members, who have a 50% chance to inherit the same mutation.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 BAP1 mutations can also be inherited, and individuals with germline mutations in this gene have been widely recognized as being predisposed to the disease, although patients with a germline BAP1 mutation are associated with better prognosis. 11,12 By identifying germline mutation status solely through radiomics, clinicians can be prompted to pursue genetic testing that may not be readily conducted otherwise, 13 resulting in more streamlined patient prognostication and assessment of family members, who have a 50% chance to inherit the same mutation. 12 This novel work first explores the use of radiomics on PM patients with somatic BAP1 mutations, to determine the feasibility of future studies determining the germline mutation status from medical images.…”
Section: Introductionmentioning
confidence: 99%